(Re) generation and (Re) interpretation of Malevolence and Gender Roles in Walt Disney’s Maleficent - Khan, Dr. Amara (Journal of Research in Humanities, 2023)
Feminine villains, equally imagined and factual, are a focus of insentient gender partiality when part of their wickedness comprises the commotion of masculine power. Disney’s one of the utmost popular active villains, Maleficent, from Sleeping Beauty (1959) celebrated in her authority, deviates from flawless womanly decorum. A study of scenes including Maleficent, the “mistress of all evil” illustrates how commanding womenfolk with hubris are criticized past their offences. This exploration is adorned from a deconstruction point of view. The key emphasis of the investigation is on the method where conventional folk tales’ and fairy tales’ adversaries are transmuted into heroes/protagonists in postmodern entertaining film genres. The research methodology used is the analysis of qualitative descriptive data with an emphasis on the transformation in the main character. Maleficent’s conduct and look indicate feminine usurpation of conventional masculine authority. The antagonist moreover engages in finger pricking which pierces and draws blood out, doings linked with figurative masculine power. The claimed skill to bewitch, in unification with the implementation of forms connected with masculine ascendency, suggests that Maleficent wields supremacy over men and wields the supremacy “of” men. Distress with the means through which the woman employs magic commands echoes old qualms of sorceresses who were suspects of misappropriating masculine sway.